Development of matrix certified reference material for accurate determination of docosahexaenoic acid in milk powder. (16th April 2023) - Zhou, Jian; Yang, MengRui; Li, Fukai; Wang, Min; Zhang, Yaoguang; Wei, Min; Li, Xingjia; Qi, Xiaoru; Bai, Xiaoyun; Chai, Yanbing
Highlights: A novel milk powder CRM was developed for determination of docosahexaenoic acid. An acetylchloride-methanol method was used for the characterization of CRM. Stability evaluation of CRM under different temperatures was carried out. Characterization, homogeneity, stability and uncertainty were fully studied. Abstract: A novel matrix certified reference material (CRM) of docosahexaenoic acid in milk powder [GBW (E) 100641] was first developed. The CRM candidates was prepared by adding appropriate levels of docosahexaenoic acid to cow's milk, then powder sprayed, lyophilized, mixed, dispensed and sterilized. An optimized acetylchloride-methanol method was proposed and used for the characterization. The CRM characterization was carried out in six laboratories in accordance with ISO Guide 35 requirements. The certified value of CRM was 0.69 mg/g with an uncertainty of 0.08 mg/g ( k = 2). The CRM was sufficiently homogeneous between and within bottles and stable up to 6 month at −20℃ and 7 days below 50 ℃. The uncertainty was evaluated by combing the contributions from characterization, homogeneity and stability. Thus, the CRM can be used for quality control and method validation to ensure the accurate and reliable measurements of docosahexaenoic acid in milk for quality monitoring.